Penggunaan Klinis Aktivitas Enzim Gamma-Glutamyl Transferase (GGT) Plasma dan Potensinya sebagai Biomarker untuk Berbagai Penyakit - Benny Syahputra Gumay; Syazili Mustofa (Majority, 2020)
Gamma-Glutamil Transferase (GGT) enzyme is a widely distributed transpeptidase in various body tissues. This enzyme is located in cell membranes and cytoplasm of hepatocytes. In addition, the expressions of the GGT enzyme is found in the kidneys, lungs, pancreas, blood vessel endothelium, nerve cells, and blood plasma. It has been used routinely in clinic to diagnose liver damage caused by alcoholism. The normal value of plasma GGT activity is 0–40 U / l. Normally, the GGT activity in blood plasma is low, but liver damage or bile ducts obstruction will increase it. There were significant association between the GGT activities in plasma and various diseases such as cardiovascular disease, metabolic syndrome such as diabetes mellitus and obesity, neurological and neurodegenerative diseases and others various diseases. Related to the measurement of GGT enzyme activity is cheap and easy to do, it's very potential to be developed for marker to diagnosis, prognosis, and further evaluation of various diseases. Further studies are needed to apply it for to be an accurate biomarker for various diseases